Cheap as chips: an accessible chip off acquisition method for ball grid array (BGA) integrated circuits in digital investigations - Hadgkiss, Melissa; Morris, Sarah; Paget, Stacey; Ventress, Adrian; Norris, Karl (Elsevier, 2022)
Chip off acquisition has steadily been used in digital investigations as an advanced data acquisition technique. This method has typically been reserved for devices where less invasive methods have been unsuccessful in data recovery. After a review of available literature, limited publications were found to define and discuss a detailed chip off methodology, especially using accessible and low-cost equipment. Therefore, demonstrating a lack of knowledge share and standardisation in this space. This paper creates a methodology for chip off acquisition, that examiners can follow, using an array of equipment. The methodology was developed using accessible resources in a variety of formats and experimental research. Once constructed the method was tested in a collection of scenarios and utilised in research and consultancy. This demonstrated areas where the method was positively implemented and areas where updates could improve the overall success of the methodology. Following the evaluation, a 6-stage process was formulated: deconstruction, identification, removal, restoration, determine and perform.
Keywords: Chip off acquisition; Digital investigation; Integrated circuits